A quality by design approach for the synthesis of palmitoyl-L-carnitine-loaded nanoemulsions as drug delivery systems - E. M. Arroyo-Urea; María Muñoz-Hernando; Marta Leo-Barriga; Fernando Herranz; Ana González-Paredes (Taylor & Francis Group, 2023)
AbstractNanoemulsions (NE) are lipid nanocarriers that can efficiently load hydrophobic active compounds, like palmitoyl-L-carnitine (pC), used here as model molecule. The use of design of experiments (DoE) approach is a useful tool to develop NEs with optimized properties, requiring less experiments compared to trial-and-error approach. In this work, NE were prepared by the solvent injection technique and DoE using a two-level fractional factorial design (FFD) as model was implemented for designing pC-loaded NE. NEs were fully characterized by a combination of techniques, studying its stability, scalability, pC entrapment and loading capacity and biodistribution, which was studied ex-vivo after injection of fluorescent NEs in mice. We selected the optimal composition for NE, named pC-NEU, after analysis of four variables using DoE. pC-NEU incorporated pC in a very efficient manner, with high entrapment efficiency (EE) and loading capacity. pC-NEU did not change its initial colloidal properties stored at 4 °C in water during 120 days, nor in buffers with different pH values (5.3 and 7.4) during 30 days. Moreover, the scalability process did not affect NE properties and stability profile. Finally, biodistribution study showed that pC-NEU formulation was predominantly concentrated in the liver, with minimal accumulation in spleen, stomach, and kidneys.